Adapted Physical Activity for Breast Cancer Patients Treated with Neoadjuvant Chemotherapy and Trastuzumab Against HER2 (APACAN2): A Protocol for a Feasibility Study - Ginzac, Angeline; Bernadach, Maureen; Molnar, Ioana; Duclos, Martine; Thivat, Emilie; Durando, Xavier (Frontiers in Oncology, 2021)
Background: The standard care for HER2-positive breast cancer is chemotherapy plus a HER2-directed therapy. This can lead to treatment-induced cardiotoxicity. On the other hand, the practice of physical activity is known to improve cardiac function; thus HER2-positive breast cancer patients could draw particular benefit from physical activity during treatment. However, at the time of diagnosis for breast cancer, the majority of patients are insufficiently active according to physical activity recommendations of World Health Organisation, and it is difficult to remain or become active during the treatment. There is a lack of data in the literature on the optimal program to propose to patients to encourage them to be active during treatment. The aim of our study is to assess the feasibility of a home-based physical activity program during neoadjuvant chemotherapy and trastuzumab for HER2-positive breast cancer. Methods: The APACAN2 study is a single-centre, non-randomized interventional trial. Patients with HER2-positive breast cancer treated with anthracycline-based neoadjuvant chemotherapy and trastuzumab are eligible for enrolment. The supervised home-based physical activity program takes place during neoadjuvant chemotherapy (NACT). It combines aerobic and strengthening exercises. The primary endpoint is the proportion of patients reaching the international physical activity recommendations, i.e. 150 minutes of moderate-intensity activity per week at the end of NACT. The study started in April 2018 and seventy patients are expected to be recruited. Discussion: In the literature, the majority of studies on practice of physical activity in breast cancer focus on adjuvant chemotherapy or on the period after the end of treatment. To the best of our knowledge, the APACAN2 study is the first to evaluate a home-based physical activity program during neoadjuvant chemotherapy for HER2-positive breast cancer. Trial registration number: Clinicaltrials.gov: NCT02963363, registered on July 11, 2016. Identifier with the French National Agency for the Safety of Medicines and Health Products N°ID RCB 2016-A01344-47, registered in August 2016. Protocol: version 8, 24 February 2021.